#TITLE_ALTERNATIVE# - DWI ADIPUTRA NOVRIANTO (NIM : 13206136); Pembimbing : Prof. Dr. Ir. Tati Latifah Erawati Rajab M, ADE
This research is conducted by developing the hardware of digital holographic microscope with off-axis configuration. This hardware was utilizing the transmision type geometric formation of Mach-Zehnder interferometer configuration. The interference occurs between the reference beam and the object beam which is transmitted by the particular object. Thus, this geometric formation is suitable for observing transparent object. The hardware of digital holographic microscope with off-axis configuration was realized on the optical table. This hardware used a laser diode as the coherent monochromatic light source and a CMOS image sensor as the digital image sensor that records digital hologram. This selection was based on the consideration that both components are relatively low cost and can be easily obtainable in the market. The laser diode that was used originates from pen shaped laser pointer which emits a red light beam, while the CMOS image sensor comes from Logitech 1.3MP Webcam C500 with resolution of 1.3 megapixels. Through measurement, it was known that the wavelength of this laser diode is 656,81 nm. The test of the hardware was conducted by recording the digital hologram of object in the form of silica gel powder. Each particle of the silica gel powder is in the shape of transparent ball with average diameter of 10,1 μm. The software that was used for the digital hologram recording is Logitech Webcam Software. The image reconstruction of silica gel powder from the digital hologram that has been recorded, was using a program which has been developed in Matlab. Development of the hardware has succeeded to be realized on the optical table, by using components which are relatively low cost and can be easily obtainable in the market. The image reconstruction has succeeded to be conducted and the result could represent the characteristics of silica gel powder well. From the test, it was also proven that coherence level of the light beam of laser diode is influenced by the forward bias current of the particular laser. The laser diode starts emitting coherent light beam when the forward bias current is higher than the threshold current. The hardware is capable to record the digital hologram with good quality on the value of forward bias current of 30,18 mA. The resolution of the hardware that was developed in this research is less than 10,1 μm.